2022
DOI: 10.1021/acsearthspacechem.1c00334
|View full text |Cite
|
Sign up to set email alerts
|

Photoreductive Dissolution of Iron (Hydr)oxides and Its Geochemical Significance

Abstract: Iron (hydr)­oxides are the most abundant metal oxides, which are widespread on Earth’s surface in the major form of micro/nanoparticles. Dissolution of iron (hydr)­oxides significantly controls their compositions on Earth’s surface and is a critical step for the global Fe cycling. Photoreductive dissolution of iron (hydr)­oxides is recognized as one of the most important process for generating Fe2+ in surface water and is also a common pathway for transforming solar energy into chemical energy. This review art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 251 publications
1
11
0
Order By: Relevance
“…Fe­(II) generation in the dark occurred due to the microbial reduction process (Figure c) because almost no Fe­(II) generation was detected in the dark after autoclaving the soil (121 °C for 20 min) (Figure d). Moreover, the Fe­(II) generation in the autoclaved soil during irradiation (Figure d) confirmed that part of the Fe­(II) generation was via the abiotic photochemical processes, which has been demonstrated by previous work …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Fe­(II) generation in the dark occurred due to the microbial reduction process (Figure c) because almost no Fe­(II) generation was detected in the dark after autoclaving the soil (121 °C for 20 min) (Figure d). Moreover, the Fe­(II) generation in the autoclaved soil during irradiation (Figure d) confirmed that part of the Fe­(II) generation was via the abiotic photochemical processes, which has been demonstrated by previous work …”
Section: Resultssupporting
confidence: 85%
“…Figure a demonstrates that more NO 3 – -N was reduced in the light (13.2 mg kg –1 ) than in the dark (7.2 mg kg –1 ), inferring that the contribution of photoinduced electrons to denitrifers was 45.5%, while the contribution of electrons generated in the dark was 54.5%. The enhanced NO 3 – -N reduction may be due to photoinduced Fe­(II) generation or photoelectrons …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…109 For mechanistic interpretation of Fe(III)-citrate photochemical degradation discussed here, special consideration of multiphase photoreductive dissolution processes of colloidal surface-bound Fe III -citrate and other Fe-organic complexes in the aqueous solution should be accounted for. 108,[110][111][112] The photodegradation of oxide bound Fe III -citrate complexes leads to dissolution of Fe III -citrate, followed by Fe(III) reduction and immediate release of soluble Fe 2+ and citrate from the colloid to the aqueous solution. 108 Overall, photodegradation of the soluble and surface bound Fe III -citrate complexes was initiated through LMCT reactions 31 R1-R4 (Scheme 1) reactions are very fast, resulting in rapid reduction of Fe III to Fe II over the rst 5 min of photolysis.…”
Section: Molecular Characterization Of the Irradiated Samplesmentioning
confidence: 99%
“…In addition, the three Hochella Symposium organizers were invited by Prof. Joel Blum, Editor-in-Chief of ACS Earth and Space Chemistry , to organize and serve as Guest Editors of a virtual special issue of this journal in honor of Mike Hochella. A total of 20 peer-reviewed manuscripts were accepted for publication in this virtual special issue (), with topics ranging from mineral/water interface chemistry and mineral/organic matter nanoparticles to organic matter/soil chemistry and microbial geochemistry studies. These papers highlight the importance of nanogeoscience, mineral/aqueous solution interface chemistry, biogeochemistry, and organic matter/soil chemistry in understanding the Earth system.…”
mentioning
confidence: 99%